Telerehabilitation for Word Retrieval Deficits in Bilinguals With Aphasia: Effectiveness and Reliability as Compared to In-person Language Therapy - Peñaloza, Claudia; Scimeca, Michael; Gaona, Angelica; Carpenter, Erin; Mukadam, Nishaat; Gray, Teresa; Shamapant, Shilpa; Kiran, Swathi (Frontiers in Neurology, 2021)
Background: Bilinguals with post-stroke aphasia (BWA) require treatment options that are sensitive to their particular bilingual background and deficits across languages. However, they may experience limited access to bilingual clinical resources due to reduced availability of bilingual practitioners, geographical constraints, and other difficulties. Telerehabilitation can improve access to bilingual clinical services for BWA and facilitate the delivery of specific language treatments at distance, but more evidence on its effectiveness and reliability is needed. This study aimed to determine the equivalence of effectiveness and reliability of a semantic treatment for word retrieval deficits in BWA delivered via telerehabilitation relative to in-person therapy. Methods: We examined the retrospective data of 16 BWA who received 20 sessions of therapy based on semantic feature analysis for word retrieval deficits in person (n = 8) or via telerehabilitation (n = 8). The two groups were comparable on age, years of education, time of post-stroke onset, aphasia severity, and naming ability in both languages. Treatment effectiveness (i.e., effect sizes in the treated and the untreated language, and change on secondary outcome measures) and reliability (i.e., clinician adherence to treatment protocol) were computed for each delivery modality and compared across groups. Results: Significant improvements were observed in most patients, with no significant differences in treatment effect sizes or secondary outcomes in the treated and the untreated language between the teletherapy group and the in-person therapy group. Also, the average percentage of correctly delivered treatment steps by clinicians was high for both therapy delivery methods with no significant differences between the telerehabilitation vs. the in-person modality. Discussion: This study provides evidence of the equivalence of treatment gains between teletherapy and in-person therapy in BWA and the high reliability with which treatment for word retrieval deficits can be delivered via telerehabilitation, suggesting that the essential treatment components of the intervention can be conducted in a comparable manner in both delivery modalities. We further discuss the benefits and potential challenges of the implementation of telerehabilitation for BWA. In the future, telerehabilitation may increase access to therapy for BWA with varying linguistic and cultural backgrounds, thus, offering a more inclusive treatment approach to this population.